120 The Instantaneous Wave-Free Ratio (IFR) Is An Accurate Predictor of Fractional Flow Reserve (FFR) In Adult Coronary Arteries so Long As a Grey Zone or Hybrid-Approach is used and not Individual Cut-Offs: The Blackpool Coronary IFR (Bcis) Study. (6th June 2015) - Galasko, Gavin
Abstract : Background: Fractional flow reserve (FFR) can be used in the cath lab to assess coronary arteries for ischaemia. To calculate an FFR adenosine needs to be given. The IFR (instantaneous free-wave ratio) has been mooted as an adenosine-independent cath-lab measure of ischaemia, derived using coronary artery wave-intensity analysis. Once validated it may thus reduce patient discomfort and procedural cost. Two approaches have been mooted when using iFR namely a) a single cut-off (iFR < = 0.89 taken as abnormal) or b) a hybrid approach (iFR <0.86 abnormal, iFR > 0.93 normal and iFR 0.86–0.93 borderline). In borderline cases adenosine should be given and FFR calculated instead. No study has prospectively assessed these two approaches to assess the validity of iFR in predicting FFR. Methods: Consecutive patients undergoing an FFR study in the cath lab underwent an iFR measurement first. Two iFR measurements were taken in the first 25 cases to assess iFR reproducibility. Adenosine was then given in all cases and an FFR was measured. The patients were managed according to the FFR result. Two iFR approaches were compared: a) a single cut-off of iFR < = 0.89 taken as abnormal vs b) the hybrid approach with iFR <0.86 abnormal, iFR 0.86–0.93 borderline and adenosine given and FFR calculated, and iFR >0.93 normal. Results: In a preliminary analysis (more data will be available for the meeting), data was collected in 20 patients (12 men (60%), mean age 63 years (range 47–87)) and 41 coronary arteries. Mean FFR was 0.84 (range 0.55–0.98). 13 arteries (32%) had an abnormal FFR (< = 0.80). Mean iFR was 0.93 (range 0.48–1.04). 10 (24%) had an iFR <0.89; 5 (12%) an iFR <0.86; 20 (49%) an iFR >0.93, and 16 (39%) iFR 0.86–0.93 (borderline). Of the 16 borderline cases, 7 (44%) had FFR < = 0.80. iFR was highly reproducible with 95% limits of agreement +0.01 to – 0.015. The correlation between iFR and FFR was excellent with R 2 0.76. The sensitivity, specificity, PPV, NPV, overall accuracy and Kappa value of agreement comparing single cut-off vs hybrid approach were 53% vs 92%; 89% vs 100%; 70% vs 100%; 81% vs 97%, 78% vs 98%, and 0.46 vs 0.94 respectively. Thus the hybrid approach was superior at each value. Conclusions: iFR measurements are quick to obtain and highly reproducible. iFR showed excellent correlation with FFR. There was only 78% agreement between iFR and FFR when using a single cut-off approach. This improved to 98% when using the hybrid approach. This approach consists of only giving adenosine and measuring FFR for borderline iFR values (iFR 0.86–0.93). Higher iFR values (>0.93) can be taken as normal and lower iFR values (<0.86) can be taken as abnormal. There was a false positive rate of only 3% and a false negative rate of 0% using the hybrid approach. 61% of cases fell outside the grey zone in consecutive patients and thus adenosine use could potentially be reduced by 61% and accuracy maintained if using the iFR and hybrid approach.